2022
DOI: 10.1111/cdev.13817
|View full text |Cite
|
Sign up to set email alerts
|

Reading to learn? The co‐development of mathematics and reading during primary school

Abstract: Understanding how early reading and mathematics co-develop is important from both theoretical and pedagogical standpoints. Previous research has provided mixed results. This paper investigates the development of reading and mathematics in a longitudinal sample of N = 355,883 students from the United Kingdom (2005-2019) aged 5 to 12 (49% girls). Results indicate a positive relation between the development of the two domains. In addition, a substantial statistically significant positive association between prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The researchers found that good reading performance predicts changes in mathematics performance, affecting students with weak mathematics performance positively. These studies concluded that reading skills seem to be predictive of mathematics development (Erbeli et al, 2021;Hübner et al, 2022).…”
Section: Mathematics and Reading Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The researchers found that good reading performance predicts changes in mathematics performance, affecting students with weak mathematics performance positively. These studies concluded that reading skills seem to be predictive of mathematics development (Erbeli et al, 2021;Hübner et al, 2022).…”
Section: Mathematics and Reading Developmentmentioning
confidence: 99%
“…The decision to parallelly evaluate two interventions stems from an interest in investigating if extensive training in one content area affects outcomes in the other as mathematics and reading development and learning seem related (Erbeli et al, 2021;Hübner et al, 2022;Peng et al, 2020). The overall project design offered a unique opportunity to study transfer of effects of intervention in addition to the expected impact on reading and mathematics skills respectively.…”
Section: Strategy and Overall Aimmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies should aim to investigate developmental changes in the predictive patterns in more detail. Furthermore, even though the association between reading and arithmetic appears to be quite stable throughout development [103][104][105][106], it will be important to investigate predictive patterns in older age groups.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%